Molecular detection of porcine circovirus type 3 in Shanxi Province, China - Weidong Yue; Yihui Liu; Xinrong Zhang; Haili Ma; Junping He (BMC, 2021)
Abstract Porcine circovirus type 3 (PCV3), which was first detected in the United States of America in 2015, is a potential threat to the swine industry. However, the prevalence of PCV3 in Shanxi Province, China, is unclear. In this research, the prevalence and genetic diversity of PCV3 were investigated in above area. Lung tissue samples (n = 491) from 19 pig slaughterhouses across 11 cities throughout Shanxi Province were analyzed for PCV3 infection by PCR in 2019. The results showed that PCV3 positive rates in slaughterhouses and individuals were 100% (19/19) and 86.76% (426/491), respectively. PCV2 and PCV3 double-positive rates in slaughterhouses and individuals were 100% (19/19) and 59.27% (291/491), respectively. PCR positive samples were further sequenced and 8 PCV3 isolates were identified. The nucleotide homology of these isolates with other PCV3 isolates in NCBI database was 97.45-99.90%. A phylogenetic analysis, based on the complete genomic sequence and ORF2, divided these PCV3 strains into 2 major groups. Based on A24/V and R27/K amino acid mutations of capsid protein, the 8 identified PCV3 strains were separated to 2 clades. This was the first detailed investigation into the epidemiology of PCV3 in Shanxi Province. Our findings enabled us to assess the possibility of widespread transmission from this region. Thus, current findings establish a basis for further studies of genetic variations in PCV3 strains circulating in China.